Prevalence of underweight, overweight and obesity among mothers in Yangon and Ayeyarwady, October–November 2023 - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
In this research note, we report results on the prevalence of underweight, overweight and obesity among mothers of young children using data collected in Yangon and Ayeyarwady as part of the Rural-Urban Food Security Survey (RUFSS). This in-person study, conducted between October–November 2023, surveyed mothers who were registered from antenatal clinics in peri-urban Yangon in early 2020. In this latest survey round, we revisited this sample of mother-child pairs to gather anthropometric data (along with other nutrition-relevant indicators). We successfully collected anthropometric data for 646 mothers.